Antigen-specific cytokine profiles for pulmonary Mycobacterium avium complex disease stage diagnosis - Yamashita, Yoshiro; Yasuda, Ikkoh; Tanaka, Takeshi; Ikeda, Toru; Terada, Mayumi; Takaki, Masahiro; Tsuchihashi, Yoshiko; Asoh, Norichika; Ohara, Yukiko; Enany, Shymaa; Kobayashi, Haruka; Matsumoto, Sohkichi; et al. (Frontiers in Immunology, 2023)
Introduction Controlling pulmonary Mycobacterium avium complex (MAC) disease is difficult because there is no way to know the clinical stage accurately. There have been few attempts to use cell-mediated immunity for diagnosing the stage. The objective of this study was to characterize cytokine profiles of CD4+T and CD19+B cells that recognize various Mycobacterium avium-associated antigens in different clinical stages of MAC. Methods A total of 47 MAC patients at different stages based on clinical information (14 before-treatment, 16 on-treatment, and 17 after-treatment) and 17 healthy controls were recruited. Peripheral blood mononuclear cells were cultured with specific antigens (MAV0968, 1160, 1276, and 4925), and the cytokine profiles (IFN-γ, TNF-α, IL-2, IL-10, IL-13, and IL-17) of CD4+/CD3+ and CD19+ cells were analyzed by flow cytometry. Results The response of Th1 cytokines such as IFN-γ and TNF-α against various antigens was significantly higher in both the on-treatment and after-treatment groups than in the before-treatment group and control (P < 0.01–0.0001 and P < 0.05–0.0001). An analysis of polyfunctional T cells suggested that the presence of IL-2 is closely related to the stage after the start of treatment (P = 0.0309-P < 0.0001) and is involved in memory function. Non-Th1 cytokines, such as IL-10 and IL-17, showed significantly higher responses in the before-treatment group (P < 0.0001 and P < 0.01–0.0001). These responses were not observed with purified protein derivative (PPD). CD19+B cells showed a response similar to that of CD4+T cells. Conclusion There is a characteristic cytokine profile at each clinical stage of MAC.